Prevalence and risk factors for postoperative ileus in colorectal cancer patients: a systematic review and meta-analysis - Guo, Dongqing; Peng, Shanshan; An, Wenzhuo; Yu, Jiayan; Chu, Xin (Frontiers in Oncology, 2026)
BackgroundPostoperative ileus (POI) is a common complication following colorectal cancer surgery, with its incidence and risk factors remaining controversial. This study aims to investigate the overall prevalence of POI in colorectal cancer patients and its risk factors through a meta-analysis.MethodsA systematic search was conducted in the Web of Science, Cochrane Library, PubMed, and Embase databases from their inception to August 7, 2025. Two researchers independently screened studies, extracted data, and assessed the risk of bias in the included studies. Statistical analysis was performed using Stata 15.1.ResultsThirty studies involving 73,433 patients were included, with 7,463 cases of POI. The overall Prevalence of POI in colorectal cancer patients was [ES = 9%, 95% CI: 8%–11%]. Meta-analysis showed that male [OR = 2.20, 95% CI: 1.76–2.76], operative time >3 hours [OR = 1.75, 95% CI: 1.20–2.40], open surgery [OR = 2.95, 95% CI: 2.20–3.95], ileostomy [OR = 4.78, 95% CI: 2.30–9.94], previous abdominal surgery [OR = 2.21, 95% CI: 1.75–2.79], and age≥65 years [OR = 1.04, 95% CI: 1.01–1.06] may be potential risk factors for POI in colorectal cancer patients. The included studies were of high quality, and no significant publication bias was detected.ConclusionBased on existing evidence, male, operative time >3 hours, open surgery, ileostomy, previous abdominal surgery, and age≥65 years may be potential risk factors for POI in colorectal cancer patients.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251121761.